Coal Mine Workers Safety Helmet in Li-Fi Data Stored in Cloud - Vishnukumar, A.; A.Nirmal Kumar, Dr.; Velmurugan, J.; Pavithra, P.; Poornima, K.; Sabareessh, S. (International Journal of Engineering and Technology, 2026)
Coal miners are more likely affected by the various threats like gas explosion ,sudden health changes and issues, severe changes of the temperature and the moisture level .In this paper we presented the design of the smart safety helmet for the coal miner using LI-FI, this helmet will be equipped with the network of sensors such as the heartbeat sensor ,humidity sensor, gas sensor and the temperature sensor and the data from these sensors will be transmitted using light fidelity technology ,the alert messages are given to the mobile phones and also through the mail to the authorized person using IOT. Many accidents which occur in the mining industries are due to the slow data transmission or due to the loss of data which has to be transmitted, these issues can be solved by using the light fidelity technology as it is known for the fast data transmission .